2009
DOI: 10.1186/bf03353169
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial distributions of atmospheric wave energy in the equatorial stratosphere revealed by GPS radio occultation temperature data obtained with the CHAMP satellite during 2001–2006

Abstract: Using stratospheric temperature profiles derived from GPS radio occultation (RO) measurements made by the German CHAMP satellite from June 2001 to May 2006, we studied the climatological behavior of atmospheric wave activity in the tropics. The wave potential energy, E p, is calculated from temperature fluctuations with vertical scales shorter than 7 km in a longitude and latitude cell of 20° × 10° at 19–26 km. E p is then averaged every 3 months (June–July–August (JJA), September–Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The difference in the vertical shear of the Walker circulation between the Eastern and Western Hemispheres plays an important role in wave filtering, which results in zonally different wave potential energy distributions in the upper troposphere and lower stratosphere (UTLS). The model results were essentially consistent with recent results obtained from GPS radio occultation (RO) data (Alexander et al 2008b;Tsuda et al 2009). However, Kawatani et al (2009) did not study wave momentum flux and wave forcing.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…The difference in the vertical shear of the Walker circulation between the Eastern and Western Hemispheres plays an important role in wave filtering, which results in zonally different wave potential energy distributions in the upper troposphere and lower stratosphere (UTLS). The model results were essentially consistent with recent results obtained from GPS radio occultation (RO) data (Alexander et al 2008b;Tsuda et al 2009). However, Kawatani et al (2009) did not study wave momentum flux and wave forcing.…”
Section: Introductionsupporting
confidence: 91%
“…Intensive or periodic observations with fine vertical resolution have revealed characteristics of gravity waves in the tropical region (e.g., Tsuda et al 1994;Maruyama 1994;Sato et al 1994;Sato and Dunkerton 1997;Wada et al 1999). Radiosonde observations have revealed that momentum transported by short-period (#;3 days) gravity waves is comparable to that transported by long-period Kelvin waves (Maruyama 1994;Sato and Dunkerton 1997).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the simulation results, the GWF parameterization assumes a seasonally constant GW source, releasing the simulated QBO from annual synchronization. Observations show strong seasonal changes in convection and GWs (e.g., Tsuda et al 2009). …”
Section: Summary and Discussionmentioning
confidence: 99%
“…That is, if G in the CCM had as clear seasonality as X in the JRA-25 data, the CCM would exhibit the annual synchronization tendency of the QBO. Observations have shown that GW activity, in fact, differs among seasons reflecting convective activity (e.g., Tsuda et al 2009). …”
Section: Mri Ccm Simulation Datamentioning
confidence: 99%